Papua New Guinea : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reviews economic developments in Papua New Guinea during 1995-97. The nonmineral sector was characterized by uneven growth. Following a period of slow growth at the time of the Bougainville crisis (1989-90), nonmineral growth began to pick up, averaging 5 1\2 percent during 1991-94. However, nonmineral output declined some 1 percent in 1995 following the onset of the financial crisis in 1994, recovered strongly in 1996 with the restoration of macroeconomic stability, and is estimated to have stagnated in 1997 owing primarily to the impact of adverse weather conditions on agricultural output.